Impacts of tenure security and market-oriented allocation of farmland on agricultural productivity: Evidence from China's apple growers. (March 2021) - Li, Xingguang; Liu, Jundi; Huo, Xuexi
Highlights: Agricultural productivity in rented plots was not significantly lower than that in owned plots. Longer-term rental contract significantly increased yield in rented plots by enhancing investment. Farmland market participation transferred farmland from low-productivity farmers to high-productivity farmers. Expanding farm size increased the number of agricultural machines input, which improved productivity. Abstract: Whether impacts of tenure insecurity and thin farmland rental markets on agricultural productivity were significant or not was still a key issue that needed to be empirically answered for most developing countries. Thus, the main objectives of this paper were to analyze the influencing mechanisms of tenure security and market-oriented allocation of farmland on agricultural productivity. We collected 762 household-level and 1163 plot-level survey data from China's apple growers. The results indicated that: (i) agricultural productivity in rented plots was not significantly lower than that in owned plots due to insignificant negative impacts of rented plots on agricultural investment. Further, longer-term farmland rental contract significantly increased yield in rented plots by enhancing agricultural investment; (ii) farmland rental market participation could transfer farmland from low-productivity farmers to high-productivity farmers, and expanding farm size was conducive to increasing the number of agricultural machines input, which improved agricultural productivity. Based on our empirical findings, we suggest that (i) central government should continue to expand and improve the reforms of farmland property rights systems; (ii) long-term farmland rental contract should be encouraged in practice, and relevant laws and regulations should be improved; (iii) the role of rural collective economic organization (RCEO) should be fully employed to reduce execution costs of farmland rental contract; (iv) farmland rental markets should be actively developed, and the costs of agricultural machines input should be reduced.